Gametogenesis, gonadal recrudescence, restraint and spawning patterns in Nile perch, Lates niloticus (Linnaeus, 1758) - Kahwa, David (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2013)
The Nile perch, Lates niloticus (Linnaeus, 1758), is a predacious freshwater fish widely distributed throughout the Afro-tropic eco-zone. The species was introduced to Lake Victoria in the early 1950s and by 1980 it had dominated the fisheries of Lake Victoria. This was followed by a dramatic decrease in the Nile perch fisheries production due to uncontrolled exploitation. The purpose of this thesis is to provide fundamental knowledge that can be applied in aquaculture and fisheries management through the study of the reproductive biology of L. niloticus. The research was aimed at the studying of the diverse aspects of the reproductive biology of L. niloticus in the Lake Victoria, Ugandan populations. This included reproductive patterns in relation to proximate environmental conditions, size at sexual maturity, gonad and gamete structure, gametogenesis and induced ovulation. The size at 50% sexual maturity for female Nile perch was 59.4 cm, which is lower than the earlier reported size of greater than 90 cm total length. Male L. niloticus matured at 57.8 cm total length in Lake Victoria. Microscopy revealed that L. niloticus from Lake Victoria had one spawning period that started in November and ended in March. Type I atresia occurred at high frequency from March to June, and type III atresia was present from July to September and between November and December. Spermatogenesis in L. niloticus is cystic and sperm development is the result of asynchronous activation of the germ cells. Type II spermatozoa are simple, uni-flagellate aquasperm with no acrosome. Oogenesis in L. niloticus differed from that of other fishes in that no cortical alveoli were present in any stage of oogenesis. Numerous oil globules were present in the primary yolk vesicle stage. This formed one centrally positioned, large oil globule in the tertiary yolk vesicle oocytes during final oocyte maturation. Clove oil was an effective sedative and an anaesthetic for the handling of L. niloticus. Induction time was more rapid at clove oil concentrations of 50 - 100 Î¼l Lâ »Â¹ than in fish exposed to clove oil concentrations less than 50 Î¼l Lâ »Â¹. Fish exposed to high concentrations exhibited significantly short induction times of less than 240 seconds. On average, fish recovered within 673 Â± 58 seconds for all the concentrations used. Prolonged exposure of L. niloticus to low clove oil concentrations of 2.5 - 10 Î¼l Lâ »Â¹ did not change the blood plasma cortisol, glucose, and the lactate and chloride ion concentration, relative to the control treatment. Captive breeding was attempted by conducting induced spawning experiments. Only final oocyte maturation was achieved using a decapeptide Gonadotropin Releasing Hormone (Dargin, sGnRH-MET), combined with a water-soluble dopamine receptor antagonist metoclopramide. This thesis suggests a research approach that provides a basis for aquaculture of the new species by first studying reproductive biology patterns and then linking the information to gonad and gamete structure so that spawning times can be estimated. It further provides insights into aspects of the reproductive biology of the species and the effects of hormonal intervention on oocytes by showing at which stage of oocyte development hormones should be applied in L. niloticus. Clove oil can be used to sedate and anaesthetise L. niloticus broodfish to reduce the stress related to the handling of large specimens.
Keywords: Nile perch -- Victoria, Lake; Gametogenesis; Oogenesis; Spermatogenesis; Nile perch -- Spawning -- Victoria, Lake; Nile perch -- Induced spawning -- Victoria, Lake; Nile perch -- Reproduction -- Endocrine aspects -- Victoria, Lake; Fish culture -- Victoria, Lake